Islam, Ideology, and the State in Bangladesh - Alam, S. M. Shamsul (Journal of Asian and African studies, 1993)
Abstract By using historical specificity as a concept this paper attempts to show the relationship between the postcolonial state of Bangladesh and ideology. The main argument of the paper is that, due to the petty bourgeoisie origin of the Bangladesh state, the hegemonic class within the state apparatus failed to enact an appropriate ideological ensemble through which the hegemonic class could reproduce itself as a class. This problem is further complicated by the heterogeneity of the middle class where various factions compete with each other to put their own ideological imprint on the state which results in chronic instability of the state. The first section of the paper explains the specificity of Bengali islam on the basis of historical narratives. The last two sections deal with the Awami League's (1971-1975) ideological construct, i.e., secularism and the military regime's (1975-1990) attempts to put Islam at the core of its ideological construct.